Virtual reality and augmented reality : 14th EuroVR International Conference, EuroVR 2017, Laval, France, December 12-14, 2017, Proceedings /: 14th EuroVR International Conference, EuroVR 2017, Laval, France, December 12-14, 2017, Proceedings. (2017) - Unknown
No abstract available